PRODUKSI PERTANAMAN CAMPURAN ANTARA Brachiaria decumbens DAN Pueraria phaseoloides BERMIKORIZA DENGAN PEMBERIAN KOMPOS CAIR - Taufan Purwokusumaning Daru, Soedarmadi Hardjosoewignjo, Luki Abdullah, Yadi Setiadi, Riyanto (Universitas 17 Agustus 1945 Samarinda, 2012)
The objective of the experiment was to find out the forage production from mix culture of mycorrhizal signal grass (B. decumbens) and puero (P. phaseoloides) which amended with liquid compost. Experiment was done in wood box 1.5 m x 1.5 m x 30 cm that filled with soil from location of experiment that was at Sangatta at PT Kaltim Prima Coal (KPC) site of East Kutai Regency. Experiment was arranged by Randomized Block Design with factorial. The first factor was mix culture of signal-puero with ratio 40% signal + 60% puero (c1), 50% signal + 50% puero (c2), and 60% signal + 40% puero, and the second factor was combination of AMF-liquid compost, those were non AMF + non liquid compost (d1), AMF + non liquid compost (d2), non AMF + liquid compost (d3), and AMF + liquid compost (d4). AMF was inoculated by seed coating technique. Result of this experiment showed that mix culture of signal-puero affect significantly different on forage dry matter production, forage P production, spore density of signal rhizosphere (P < 0.01), CP of forage production, and spore density of puero rhizosphere (P < 0.05), but not significantly different (P > 0.05) on signal and puero CP content, signal and puero CF content, signal and puero P content, forage CF production, signal and puero AMF colonization. Whereas, combination of AMF-liquid compost gave effect to forage dry matter production, signal CP content, puero CF content, puero P content, forage CP production (P < 0.05), and signal and puero AMF colonization (P < 0.01). There was not interaction between mix culture of signal-puero and combination of AMF-liquid compost. Generally, highest quantity and quality of forage production was achieved on mix culture of 40 % signal and 60 % puero, meanwhile combination of AMF-liquid compost was obtained on treatment AMF+liquid compost. Mix culture of 40 % signal and 60 % puero may be accepted as pasture on grazing land.